Appling Power BI for improved retail business analytics and decision-making - Huu DANG QUOC (Applied Computer Science)
In the rapidly evolving retail industry, data-driven decision making is critical to maintaining competitive advantage and operational efficiency. This paper explores the diverse applications of Microsoft Power BI (MPBI) in retail, highlighting its impact on real-time data management, sales analysis, inventory optimization, customer insights, and supply chain performance. By synthesizing findings from recent studies and presenting empirical data from case studies, we demonstrate how Power BI's advanced analytics and visualization capabilities can transform raw data into actionable insights. Our research underscores the importance of integrating disparate data sources into a unified platform, facilitating comprehensive data analysis, and fostering a culture of data literacy across retail organizations. We also discuss the challenges and best practices for implementing Power BI across retail functions, highlighting its role in driving innovation and adapting to emerging market trends. The results of this study provide practical insights for retailers seeking to leverage data analytics for strategic decision-making and operational excellence.